The importance of gender on coronary artery size: In‐vivo assessment by intravascular ultrasound - Kim, Sang‐Gon (Clin Cardiol, 2006)
Background: It remains controversial whether women have smaller coronary arteries than men because of a gender‐specific trait, or whether the observed differences are primarily due to a difference in body size. Intravascular ultrasound (IVUS), with its ability to provide unique coronary images that allow precise measurement of arterial size in vivo, is ideally suited to address this issue. Hypothesis: Female gender, independent of body size, is associated with smaller coronary artery size as measured by intracoronary ultrasound. Methods: Intravascular ultrasound images of normal left main arteries were identified retrospectively from a single center database. Associations between demographic and clinical characteristics (including body size) and left main coronary dimensions were assessed with univariant and multivariate regression analyses. Results: We identified 257 completely normal left main arteries. Mean left main arterial areas were smaller in women than in men (17.2 vs. 20.6 mm(2), p < 0.001), as were mean luminal areas (14.0 vs. 16.7 mm(2), p < 0.001). By multiple regression analysis, the independent predictors of left main lumen were body surface area (p < 0.001) and gender (p = 0.003). Conclusions: Body surface area and gender are both independent predictors of coronary artery size, although body size has a greater influence than gender.